Development of The Paternalist Leadership Behavior Scale of School Principals: Validity and Reliability Study - İnayet Aydın; Ahmet Saylık (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
As an organizational and managerial approach, paternalist leadership is generally considered as a positive value and a functional approach by relying on a deep cultural heritage in Asian societies. Although the concept of studies aimed at determining the dimensions of paternalist leadership has generally limited to benevolent, morality and authoritarianism, it is stated that paternal approaches are essentially exploitative, have some limitations on autonomy, contain some kind of interventionism, find the beneficiary insufficient, and mask the authoritarianism with the compassion and love of the father. The aim of this study is to develop a reliable and valid measurement tool to measure the paternalist behavior of school principals. For this purpose, 245 teachers working in primary schools in Ankara, Mamak, Gölbaşı and Çankaya district centers were applied. Expert opinions were used for the scope validity of the study. As a result of the Exploratory Factor Analysis (EFA) applied for the construct validity of the study, the variance explained by the scale was determined as 67.16 % and a structure consisting of 5 factors was obtained. According to the results of Confirmatory Factor Analysis (CFA) conducted to confirm the AFA results, the fit index of the 5-factor structure was found to be at a good level. On the other hand, Cronbach’s Alpha coefficient was used for the reliability analysis of the paternalist leadership scale, and the corrected item total correlations for the distinguishing characteristics of the scale items were examined and it was found that the scale was a reliable measurement tool.